(untitled) (Indian Journal of Animal Production and Management, 2014)
Data on the body weight and biometrical measurements of 1204 sheep were collected at random from four different districts of Andhra Pradesh. Least-squares analysis was conducted to study the influence of district and age on body weights and biometrical measurements and the data adjusted for the district effect were utilized for the estimation of phenotypic correlations. The phenotypic correlations between body weight and the height at withers, chest girth, paunch girth, hip width, body length were all found to be positive, moderate to high in magnitude and highly significant at all ages. The coefficients of determination (R2 values) ranged from 57 to 72, 50 to 61, 58 to 68 and 66 to 74 per cent at 2, 4, 6 and 8-tooth age animals respectively indicating a reasonable precision in predicting body weights based on body measurements. The results of the study revealed that the prediction equations involving chest girth and height at withers could be reasonably used for estimating body weights of Macherla Brown sheep under field conditions.